2012
DOI: 10.1007/s00395-012-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 in the heart: expression, regulation and functional role in ischemia

Abstract: Aquaporins (AQPs) are channel-forming membrane proteins highly permeable to water. AQP4 is found in mammalian hearts; however, its expression sites, regulation and function are largely unknown. The aim was to investigate cardiac AQP4 expression in humans and mice, its regulation by ischemia and hypoxia, and in particular its role in cardiac ischemic injury using AQP4 knockout (KO) mice. Comparable levels of AQP4 were detected by Western blot and qPCR in biopsies from human donor hearts and wild type C57Bl6 mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Based on the demonstrated role of AQP4 during brain and heart ischemia (14, 26), we hypothesized that AQP4 blockade ameliorates the consequences of ischemia reperfusion injury and thus extends transplant survival. Unexpectedly, AQP4 inhibition did not alter the intragraft expression of inflammatory markers typically found in ischemia/reperfusion injury at 24 h posttranspant including cytokines TNFα, IL-1β, IL-6, chemokines CXCL1, CXCL2, and CCL2, and adhesion molecule ICAM-1 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the demonstrated role of AQP4 during brain and heart ischemia (14, 26), we hypothesized that AQP4 blockade ameliorates the consequences of ischemia reperfusion injury and thus extends transplant survival. Unexpectedly, AQP4 inhibition did not alter the intragraft expression of inflammatory markers typically found in ischemia/reperfusion injury at 24 h posttranspant including cytokines TNFα, IL-1β, IL-6, chemokines CXCL1, CXCL2, and CCL2, and adhesion molecule ICAM-1 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Our study was prompted by recent findings that AQP4 is expressed on cardiac myocytes and is protective during ischemic cardiac tissue injury (14). Treatment of donor hearts with the AQP4 inhibitor during collection, perfusion and storage significantly reduced the rate of cellular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other works demonstrated that AQP4 KO mice undergoing global ischemia and reperfusion had reduced infarct size and attenuated left ventricular end-diastolic pressure during reperfusion after cardiac ischemic injury [15]. Also AQP4 KO cardio-myocytes were partially resisted to hypoosmotic stress in the presence of hypercontracture of the left coronary artery [15]. Other evidences indicate that Diazoxide (a mitochondrial KATPchannel opener) may have impact on myocardial water balance and glycerol uptake by decreasing the relative expression of AQP7 during coronary artery bypass grafting in patients with stable coronary artery disease [16].…”
Section: Editorial Textmentioning
confidence: 97%
“…These changes are likely due to an increase in pro-inflammatory factors (ET A , pPKCε, NADPH oxidase p67phox) which are exacerbated by stress [14]. Other works demonstrated that AQP4 KO mice undergoing global ischemia and reperfusion had reduced infarct size and attenuated left ventricular end-diastolic pressure during reperfusion after cardiac ischemic injury [15]. Also AQP4 KO cardio-myocytes were partially resisted to hypoosmotic stress in the presence of hypercontracture of the left coronary artery [15].…”
Section: Editorial Textmentioning
confidence: 99%